High-performance lithium manganese iron phosphate battery and preparation method thereof

By optimizing the content and doping ratio of lithium and manganese in lithium manganese ferrophosphate batteries, and combining semi-dry and wet processes to prepare slurries, the problems of low energy density and poor low temperature performance of lithium manganese ferrophosphate batteries are solved, and higher energy density and cycle stability are achieved.

CN119890462APending Publication Date: 2025-04-25DONG GUAN LONGTTECH COMPANY LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411913009.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Lithium manganese iron phosphate batteries have low energy density, low voltage platform and poor low temperature performance, which cannot meet the broader market demand.

Method used

By optimizing the content of lithium and manganese elements in lithium manganese phosphate, adjusting the doping ratio of manganese materials, using semi-dry process to prepare the positive electrode slurry, and using wet process to prepare the negative electrode slurry, optimizing the ratio of active substances, conductive agents and binders.

Benefits of technology

It significantly improves the low-temperature performance and energy density of the battery, enhances cycling stability and safety, and achieves higher voltage platform and charge and discharge power.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890462A_ABST
    Figure CN119890462A_ABST
Patent Text Reader

Abstract

According to the high-performance lithium manganese iron phosphate battery and the preparation method thereof provided by the invention, the positive active material lithium manganese iron phosphate material is optimized, the contents of lithium element and manganese element in lithium manganese iron phosphate are optimized, and the doping proportion of the manganese material is optimized; the lithium manganese iron phosphate battery with excellent performance such as energy density, cycling stability and safety is obtained, the positive electrode slurry adopts a semi-dry process, the negative electrode slurry adopts a wet process, the uniformity of the positive electrode slurry and the negative electrode slurry produced by the two processes is better, the humidity and the temperature in the mixing process are easy to control, and the production efficiency is improved. And the ratio of the positive and negative slurry active substances, the conductive agent and the binder is optimized, so that the consistency and the stability of the slurry are improved, the low-temperature performance and the energy density of the battery are effectively improved, and the cycle performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of batteries, and in particular to a high-performance lithium manganese iron phosphate battery and a preparation method thereof. [Background technology]

[0002] With the promotion and popularization of electric vehicles in the global market, the demand for lithium iron phosphate batteries, as a battery material with high safety and long cycle life, has increased significantly. Since the performance of lithium iron phosphate batteries is particularly suitable for power applications and is internationally certified as a non-toxic and pollution-free green and environmentally friendly battery, it is widely favored and has shown its prowess in the field of power lithium-ion batteries. However, due to the low energy density, low voltage platform and poor low-temperature performance of lithium iron phosphate batteries, they cannot adapt to a wider market demand. Therefore, the future market needs a new battery solution with high energy density and performance similar to that of lithium iron phosphate batteries.

[0003] Lithium manganese iron phosphate (LMFP) is the product of the combination of lithium manganese phosphate and lithium iron phosphate. It fully combines the advantages of both, making its energy density and low-temperature performance better than LFP (lithium iron phosphate). Its high-temperature performance, safety and cost inherit the characteristics of LFP, making it better than ternary.

[0004] Although lithium iron phosphate has the advantages of easy synthesis, low cost and relatively high conductivity, and its commercialization is relatively successful, its conductivity is extremely low and its stability is poor, making it difficult to exert its advantages in a wider range of fields. The addition of manganese increases the voltage platform and thus improves the energy density, which can be increased to 21% at most, which is exactly the shortcoming of lithium iron phosphate.

[0005] However, the crystal structure of lithium iron phosphate is distorted after adding manganese, which affects the cycle and rate performance. Lithium manganese iron phosphate has the following weaknesses: when the manganese doping ratio is too high, the Jan-Taylor effect occurs. This effect is manifested as manganese ions dissolving and depositing on the surface of the negative electrode during the charge and discharge process, destroying the SEI film, causing the SEI film to continuously regenerate and repair, thereby consuming a large amount of active lithium and causing capacity loss. In addition, manganese dissolution reacts with the electrolyte, which not only affects the stability of the material, but also reduces the capacity retention rate of the material. Due to the poor conductivity of manganese, a high manganese doping ratio is also prone to cause polarization, which further reduces the cycle life. When the manganese content is too low, the platform voltage of the lithium manganese iron phosphate material is not significantly increased, affecting the energy density of the material. Therefore, finding a suitable manganese doping ratio is the key to developing high-performance lithium manganese iron phosphate batteries.

[0006] In view of this, it is necessary to provide a new type of high-performance lithium manganese iron phosphate battery and a preparation method thereof to overcome the above-mentioned defects. [Summary of the invention]

[0007] The purpose of the present invention is to provide a high-performance lithium manganese iron phosphate battery and a preparation method thereof, so as to improve the low-temperature performance and energy density of the battery.

[0008] In order to achieve the above-mentioned object, in the first aspect, the present invention provides a high-performance lithium iron manganese phosphate battery, including a positive electrode sheet, a negative electrode sheet, a separator and a steel shell, wherein the positive electrode sheet, the separator and the negative electrode sheet are wound and accommodated in the steel shell; the positive electrode sheet includes a positive electrode collector and a positive electrode slurry coated on the positive electrode collector, the positive electrode slurry includes a positive electrode active material, the positive electrode active material is lithium iron manganese phosphate, and the structural formula of the positive electrode active material is LiMn x Fe 1-x-y M y PO4, wherein 0≤x≤1, 0≤y≤1, and M is one or more of the transition metal elements Co, Ni, Mn, Zn, V and Ti.

[0009] In a preferred embodiment, the positive electrode active material has the general structural formula LiMn x Fe 1-x-y M y In PO4, 0.4≤x≤0.7, 0≤y≤0.1.

[0010] In a preferred embodiment, the positive electrode active material is an inorganic phosphate with an olivine structure.

[0011] In a preferred embodiment, the primary particle size of the positive electrode active material is 200-400 nm.

[0012] In a preferred embodiment, the positive electrode slurry further includes a positive electrode conductor, a positive electrode binder, and a positive electrode dispersant. The positive electrode conductor includes one or more of CNT, SP, and graphene. The positive electrode binder is PVDF, and the positive electrode dispersant is TR-4045.

[0013] In a preferred embodiment, the negative electrode plate includes a negative electrode current collector and a negative electrode slurry coated on the negative electrode current collector, the negative electrode slurry includes a negative electrode active material, a negative electrode conductive agent, a negative electrode thickener, and a negative electrode binder, the negative electrode active material includes one or more of graphite, soft carbon, and biomass hard carbon, the negative electrode conductive agent includes one or more of carbon nanotubes, conductive carbon black, and water-based graphene composite slurry, the negative electrode thickener is CMC, and the negative electrode binder is SBR.

[0014] In a second aspect, the present invention also provides a method for preparing a high-performance lithium manganese iron phosphate battery, comprising the following steps:

[0015] Step S10, preparing a positive electrode sheet: mixing powders of a positive electrode active material, a positive electrode conductive agent, a positive electrode binder PVDF, and a positive electrode dispersant, kneading and stirring them evenly; adding part of the NMP solvent to wet the powder particles, dispersing the particle agglomerates under the action of high-speed shear force, so that the positive electrode conductive agent is evenly distributed, and the slurry is in a wet and viscous mud-like state; after kneading, adding the NMP solvent to adjust the viscosity and solid content of the slurry to form a black, wet and viscous colloid, and then preparing a positive electrode slurry of a PVDF / NMP oily system; coating the positive electrode slurry on the positive electrode collector, rolling and forming, and obtaining a positive electrode sheet; the positive electrode active material is lithium iron manganese phosphate, and the structural formula of the positive electrode active material is LiMn x Fe 1-x-y M y PO4, wherein 0≤x≤1, 0≤y≤1, and M is one or more of transition metal elements Co, Ni, Mn, Zn, V and Ti;

[0016] Step S20, preparing the negative electrode sheet: mixing and stirring the negative electrode active material hard carbon and the negative electrode thickener CMC glue to make the slurry into a wet and viscous mud, adding the negative electrode conductive agent water-based graphene composite slurry and solvent, wetting and kneading the powder particles and controlling the slurry viscosity, and then adding the negative electrode binder SBR, dispersing the particle agglomerates under the action of high-speed shear force, so that the negative electrode active material and the negative electrode conductive agent are evenly distributed to form a light gray and viscous liquid, and preparing a negative electrode slurry of a hard carbon / CMC / SBR aqueous system, coating the negative electrode slurry on the negative electrode collector, and roller-forming to obtain a negative electrode sheet;

[0017] Step S30, cutting the formed positive electrode sheet and negative electrode sheet into positive electrode rolls and negative electrode rolls, welding the pole ears on the positive electrode rolls and negative electrode rolls, adding a separator between the positive electrode sheet and the negative electrode sheet, winding them, and assembling them into a steel shell;

[0018] Step S40, baking the assembled battery cells, injecting electrolyte into the steel shell and sealing the steel shell to obtain a finished battery, and then chemically dividing the finished battery into different capacities.

[0019] In a preferred embodiment, in step S10, the positive electrode conductive agent includes SP and CNT, and the weight ratio of the positive electrode active material, SP, CNT, positive electrode binder and positive electrode dispersant is 79.6:1.3:16.7:2:0.4.

[0020] In a preferred embodiment, in step S20, the weight ratio of the solid content of the negative electrode active material, the negative electrode conductive agent, the negative electrode thickener, and the negative electrode binder is 94.95:1.5:1.35:2.2.

[0021] In a preferred embodiment, the tap density of the positive electrode active material is ≥ 0.8 g / cm 3 , with a specific surface area of ​​19-25m 2 / g; during the preparation of the positive electrode active material, the primary particle size of the added lithium source and manganese source is 60-100nm.

[0022] Compared with the prior art, the high-performance lithium iron manganese phosphate battery and the preparation method thereof provided by the present invention optimize the lithium iron manganese phosphate material of the positive electrode active material, optimize the contents of lithium and manganese in the lithium iron manganese phosphate, and optimize the doping ratio of the manganese material, so as to obtain a lithium iron manganese phosphate battery with excellent performances such as energy density, cycle stability, and safety. The positive electrode slurry adopts a semi-dry process, and the negative electrode slurry adopts a wet process. The positive and negative electrode slurries produced by the two processes have better uniformity, and it is easy to control the humidity and temperature during the mixing process. The active materials, conductive agents and binders in the positive and negative electrode slurries are optimized, which improves the consistency and stability of the slurry, effectively improves the low temperature performance and energy density of the battery, and has excellent cycle performance.

Brief Description of the Drawings

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0024] Figure 1 The present invention provides a flow chart of a method for preparing a high-performance lithium manganese iron phosphate battery. [Specific implementation method]

[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. The components of the embodiments of the present invention generally described and shown in the drawings here can be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the claimed invention, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present invention.

[0026] The present invention provides a high-performance lithium manganese iron phosphate battery. By optimizing the lithium manganese iron phosphate material, which is a positive electrode active material, and optimizing the doping ratio of the manganese material, a lithium manganese iron phosphate active material with a better ratio of manganese iron phosphate doped with the manganese material is used to improve its cycle life and cycle stability, stably improve its voltage platform, and effectively improve the low-temperature performance and energy density of the battery.

[0027] The high-performance lithium iron manganese phosphate battery provided by the present invention comprises a positive electrode sheet, a negative electrode sheet, a separator and a steel shell, wherein the positive electrode sheet, the separator and the negative electrode sheet are wound and accommodated in the steel shell; the positive electrode sheet comprises a positive electrode current collector and a positive electrode slurry coated on the positive electrode current collector, the positive electrode slurry comprises a positive electrode active material, the positive electrode active material is lithium iron manganese phosphate, and the structural formula of the positive electrode active material is LiMn x Fe 1-x-y M y PO4, wherein 0≤x≤1, 0≤y≤1, and M is one or more of the transition metal elements Co, Ni, Mn, Zn, V and Ti.

[0028] Furthermore, the positive electrode active material has a general structural formula of LiMn x Fe 1-x-y M y In PO4, 0.4≤x≤0.7, 0≤y≤0.1, the positive electrode active material is an inorganic phosphate with an olivine structure. That is, the positive electrode active material includes several lithium manganese iron phosphate compounds with different spatial structures formed by doping lithium manganese iron phosphate with manganese elements of different molar masses, specifically an inorganic phosphate with an olivine structure, and the primary particle size of the positive electrode active material is less than 500nm, preferably 200-400nm.

[0029] The positive electrode slurry also includes a positive electrode conductor, a positive electrode binder, and a positive electrode dispersant. The positive electrode conductor includes one or more of CNT, SP, and graphene, preferably a combination of CNT and SP. The positive electrode binder is preferably PVDF, and the positive electrode dispersant is preferably TR-4045.

[0030] The negative electrode sheet includes a negative electrode current collector and a negative electrode slurry coated on the negative electrode current collector, and the negative electrode slurry includes a negative electrode active material, a negative electrode conductive agent, a negative electrode thickener, and a negative electrode binder. The negative electrode active material includes one or more of graphite, soft carbon, and biomass hard carbon, preferably biomass hard carbon. The negative electrode conductive agent includes one or more of carbon nanotubes, conductive carbon black, and water-based graphene composite slurry, preferably water-based graphene composite slurry. The negative electrode thickener is preferably CMC, and the negative electrode binder is preferably SBR.

[0031] See also Figure 1, which is a flow chart of the method for preparing a high-performance lithium manganese iron phosphate battery provided by the present invention. The method for preparing a high-performance lithium manganese iron phosphate battery provided by the present invention comprises the following steps:

[0032] Step S10, preparing a positive electrode sheet: mixing powders of a positive electrode active material, a positive electrode conductive agent, a positive electrode binder PVDF, and a positive electrode dispersant, kneading and stirring them evenly; adding part of the NMP solvent to wet the powder particles, dispersing the particle agglomerates under the action of high-speed shear force, so that the positive electrode conductive agent is evenly distributed, and the slurry is in a wet and viscous mud-like state; after kneading, adding the NMP solvent to adjust the viscosity and solid content of the slurry to form a black, wet and viscous colloid, and then preparing a positive electrode slurry of a PVDF / NMP oily system; coating the positive electrode slurry on the positive electrode collector, rolling and forming, and obtaining a positive electrode sheet; the positive electrode active material is lithium iron manganese phosphate, and the structural formula of the positive electrode active material is LiMn x Fe 1-x-y M y PO4, wherein 0≤x≤1, 0≤y≤1, and M is one or more of transition metal elements Co, Ni, Mn, Zn, V and Ti;

[0033] Step S20, preparing the negative electrode sheet: mixing and stirring the negative electrode active material hard carbon and the negative electrode thickener CMC glue to make the slurry into a wet and viscous mud, adding the negative electrode conductive agent water-based graphene composite slurry and solvent, wetting and kneading the powder particles and controlling the slurry viscosity, and then adding the negative electrode binder SBR, dispersing the particle agglomerates under the action of high-speed shear force, so that the negative electrode active material and the negative electrode conductive agent are evenly distributed to form a light gray and viscous liquid, and preparing a negative electrode slurry of a hard carbon / CMC / SBR aqueous system, coating the negative electrode slurry on the negative electrode collector, and roller-forming to obtain a negative electrode sheet;

[0034] Step S30, cutting the formed positive electrode sheet and negative electrode sheet into positive electrode rolls and negative electrode rolls, welding the pole ears on the positive electrode rolls and negative electrode rolls, adding a separator between the positive electrode sheet and the negative electrode sheet, winding them, and assembling them into a steel shell;

[0035] Step S40, baking the assembled battery cells, injecting electrolyte into the steel shell and sealing the steel shell to obtain a finished battery, and then chemically dividing the finished battery into different capacities.

[0036] Specifically, in step S10, the positive electrode conductive agent includes SP and CNT, and the weight ratio of the positive electrode active material, SP, CNT, positive electrode binder, and positive electrode dispersant is 79.6:1.3:16.7:2:0.4. In step S20, the weight ratio of the solid content of the negative electrode active material, negative electrode conductive agent, negative electrode thickener, and negative electrode binder is 94.95:1.5:1.35:2.2. The positive electrode collector can be aluminum foil, and the negative electrode collector can be copper foil. The prepared battery can be a square battery.

[0037] Furthermore, the tap density of the positive electrode active material is ≥0.8 g / cm 3 , with a specific surface area of ​​19-25m 2 / g; during the preparation of the positive electrode active material, the primary particle size of the added lithium source and manganese source is 60-100nm.

[0038] The high performance lithium manganese iron phosphate battery and the preparation method thereof provided by the present invention are tested through several embodiments below.

[0039] Embodiment 1:

[0040] Preparation of positive electrode: 6g of lithium iron manganese phosphate (LiMn x Fe 1-x-y M y PO4, x = 0.4), 0.95g SP, 1.51g PVDF dry powder, 0.32g TR-4045, 15r / min low speed dry mixing for 30min, until the dry powder is evenly mixed; add 6.31g NMP solvent, 12.62g CNT (5%) slurry, 20r / min slow stirring for 30min, scrape the material after stirring, add 7.33g NMP solvent, 20r / min medium and high speed stirring for 100min, observe the kneading state of the slurry and then determine to add 10.04g NMP solvent, 30r / min high speed stirring for 60min, measure the viscosity, fineness and solid content of the slurry out of the pot. After the solid content (64% ± 5%) and viscosity (7000-10000mpa.s) are qualified, the positive electrode slurry is coated on aluminum foil and roll-formed to obtain a positive electrode sheet.

[0041] Preparation of negative electrode sheet: Add 45g hard carbon, 26.98g 2.73% CMC glue, stir at low speed for 40min, scrape after stirring, 7.11g aqueous conductive agent solution (10%), 5g deionized water, knead and stir at 20r / min for 120min, mix evenly; add 1.9g NMP solvent, stir at 30r / min for 80min, stir at high speed to break and disperse the particle agglomerates, finally add 2.09g SBR (50%), stir at 15r / min for 30min, adjust the viscosity after fully mixing, and obtain negative electrode slurry. Apply the slurry on copper foil, roll-form, and obtain negative electrode sheet.

[0042] The formed positive and negative electrode sheets are cut into positive electrode rolls and negative electrode rolls, the pole ears are welded on the electrode rolls, and a separator is added between the positive and negative electrode sheets for winding and assembly into a steel shell.

[0043] The assembled battery cells are baked, electrolyte is injected, and the batteries are sealed. The finished batteries are then divided into different capacities.

[0044] Embodiment 2:

[0045] Preparation of positive electrode: 6g of lithium iron manganese phosphate (LiMn x Fe 1-x-y M y PO4, x = 0.45), 0.95g SP, 1.51g PVDF dry powder, 0.32g TR-4045, 15r / min low speed dry mixing for 30min, until the dry powder is evenly mixed; add 6.31g NMP solvent, 12.62g CNT (5%) slurry, 20r / min slow stirring for 30min, scrape the material after stirring, add 7.33g NMP solvent, 20r / min medium and high speed stirring for 100min, observe the kneading state of the slurry and then determine to add 10.04g NMP solvent, 30r / min high speed stirring for 60min, measure the viscosity, fineness and solid content of the slurry out of the pot. After the solid content (64% ± 5%) and viscosity (7000-10000mpa.s) are qualified, the positive electrode slurry is coated on aluminum foil and roll-formed to obtain a positive electrode sheet.

[0046] Preparation of negative electrode sheet: Add 45g hard carbon, 26.98g 2.73% CMC glue, stir at low speed for 40min, scrape after stirring, 7.11g aqueous conductive agent solution (10%), 5g deionized water, knead and stir at 20r / min for 120min, mix evenly; add 1.9g NMP solvent, stir at 30r / min for 80min, stir at high speed to break and disperse the particle agglomerates, finally add 2.09g SBR (50%), stir at 15r / min for 30min, adjust the viscosity after fully mixing, and obtain negative electrode slurry. Apply the slurry on copper foil, roll-form, and obtain negative electrode sheet.

[0047] The formed positive and negative electrode sheets are cut into positive electrode rolls and negative electrode rolls, the pole ears are welded on the electrode rolls, and a separator is added between the positive and negative electrode sheets for winding and assembly into a steel shell.

[0048] The assembled battery cells are baked, electrolyte is injected, and the batteries are sealed. The finished batteries are then divided into different capacities.

[0049] Embodiment 3:

[0050] Preparation of positive electrode: 6g of lithium iron manganese phosphate (LiMn x Fe 1-x-y M y PO4, x = 0.5), 0.95g SP, 1.51g PVDF dry powder, 0.32g TR-4045, 15r / min low speed dry mixing for 30min, until the dry powder is evenly mixed; add 6.31g NMP solvent, 12.62g CNT (5%) slurry, 20r / min slow stirring for 30min, scrape the material after stirring, add 7.33g NMP solvent, 20r / min medium and high speed stirring for 100min, observe the kneading state of the slurry and then determine to add 10.04g NMP solvent, 30r / min high speed stirring for 60min, measure the viscosity, fineness and solid content of the slurry out of the pot. After the solid content (64% ± 5%) and viscosity (7000-10000mpa.s) are qualified, the positive electrode slurry is coated on aluminum foil and roll-formed to obtain a positive electrode sheet.

[0051] Preparation of negative electrode sheet: Add 45g hard carbon, 26.98g 2.73% CMC glue, stir at low speed for 40min, scrape after stirring, 7.11g aqueous conductive agent solution (10%), 5g deionized water, knead and stir at 20r / min for 120min, mix evenly; add 1.9g NMP solvent, stir at 30r / min for 80min, stir at high speed to break and disperse the particle agglomerates, finally add 2.09g SBR (50%), stir at 15r / min for 30min, adjust the viscosity after fully mixing, and obtain negative electrode slurry. Apply the slurry on copper foil, roll-form, and obtain negative electrode sheet.

[0052] The formed positive and negative electrode sheets are cut into positive electrode rolls and negative electrode rolls, the pole ears are welded on the electrode rolls, and a separator is added between the positive and negative electrode sheets for winding and assembly into a steel shell.

[0053] The assembled battery cells are baked, electrolyte is injected, and the batteries are sealed. The finished batteries are then divided into different capacities.

[0054] Embodiment 4:

[0055] Preparation of positive electrode: 6g of lithium iron manganese phosphate (LiMn x Fe1-x-y M y PO4, x = 0.55), 0.95g SP, 1.51g PVDF dry powder, 0.32g TR-4045, 15r / min low speed dry mixing for 30min, until the dry powder is evenly mixed; add 6.31g NMP solvent, 12.62g CNT (5%) slurry, 20r / min slow stirring for 30min, scrape the material after stirring, add 7.33g NMP solvent, 20r / min medium and high speed stirring for 100min, observe the kneading state of the slurry and then determine to add 10.04g NMP solvent, 30r / min high speed stirring for 60min, measure the viscosity, fineness and solid content of the slurry out of the pot. After the solid content (64% ± 5%) and viscosity (7000-10000mpa.s) are qualified, the positive electrode slurry is coated on aluminum foil and roll-formed to obtain a positive electrode sheet.

[0056] Preparation of negative electrode sheet: Add 45g hard carbon, 26.98g 2.73% CMC glue, stir at low speed for 40min, scrape after stirring, 7.11g aqueous conductive agent solution (10%), 5g deionized water, knead and stir at 20r / min for 120min, mix evenly; add 1.9g NMP solvent, stir at 30r / min for 80min, stir at high speed to break and disperse the particle agglomerates, finally add 2.09g SBR (50%), stir at 15r / min for 30min, adjust the viscosity after fully mixing, and obtain negative electrode slurry. Apply the slurry on copper foil, roll-form, and obtain negative electrode sheet.

[0057] The formed positive and negative electrode sheets are cut into positive electrode rolls and negative electrode rolls, the pole ears are welded on the electrode rolls, and a separator is added between the positive and negative electrode sheets for winding and assembly into a steel shell.

[0058] The assembled battery cells are baked, electrolyte is injected, and the batteries are sealed. The finished batteries are then divided into different capacities.

[0059] Embodiment 5:

[0060] Preparation of positive electrode: 6g of lithium iron manganese phosphate (LiMn x Fe 1-x-y M yPO4, x = 0.6), 0.95g SP, 1.51g PVDF dry powder, 0.32g TR-4045, 15r / min low speed dry mixing for 30min, until the dry powder is evenly mixed; add 6.31g NMP solvent, 12.62g CNT (5%) slurry, 20r / min slow stirring for 30min, scrape the material after stirring, add 7.33g NMP solvent, 20r / min medium and high speed stirring for 100min, observe the kneading state of the slurry and then determine to add 10.04g NMP solvent, 30r / min high speed stirring for 60min, measure the viscosity, fineness and solid content of the slurry out of the pot. After the solid content (64% ± 5%) and viscosity (7000-10000mpa.s) are qualified, the positive electrode slurry is coated on aluminum foil and roll-formed to obtain a positive electrode sheet.

[0061] Preparation of negative electrode sheet: Add 45g hard carbon, 26.98g 2.73% CMC glue, stir at low speed for 40min, scrape after stirring, 7.11g aqueous conductive agent solution (10%), 5g deionized water, knead and stir at 20r / min for 120min, mix evenly; add 1.9g NMP solvent, stir at 30r / min for 80min, stir at high speed to break and disperse the particle agglomerates, finally add 2.09g SBR (50%), stir at 15r / min for 30min, adjust the viscosity after fully mixing, and obtain negative electrode slurry. Apply the slurry on copper foil, roll-form, and obtain negative electrode sheet.

[0062] The formed positive and negative electrode sheets are cut into positive electrode rolls and negative electrode rolls, the pole ears are welded on the electrode rolls, and a separator is added between the positive and negative electrode sheets for winding and assembly into a steel shell.

[0063] The assembled battery cells are baked, electrolyte is injected, and the batteries are sealed. The finished batteries are then divided into different capacities.

[0064] Embodiment 6:

[0065] Preparation of positive electrode: 6g of lithium iron manganese phosphate (LiMn x Fe 1-x-y M yPO4, x = 0.65), 0.95g SP, 1.51g PVDF dry powder, 0.32g TR-4045, 15r / min low speed dry mixing for 30min, until the dry powder is evenly mixed; add 6.31g NMP solvent, 12.62g CNT (5%) slurry, 20r / min slow stirring for 30min, scrape the material after stirring, add 7.33g NMP solvent, 20r / min medium and high speed stirring for 100min, observe the kneading state of the slurry and then determine to add 10.04g NMP solvent, 30r / min high speed stirring for 60min, measure the viscosity, fineness and solid content of the slurry out of the pot. After the solid content (64% ± 5%) and viscosity (7000-10000mpa.s) are qualified, the positive electrode slurry is coated on aluminum foil and roll-formed to obtain a positive electrode sheet.

[0066] Preparation of negative electrode sheet: Add 45g hard carbon, 26.98g 2.73% CMC glue, stir at low speed for 40min, scrape after stirring, 7.11g aqueous conductive agent solution (10%), 5g deionized water, knead and stir at 20r / min for 120min, mix evenly; add 1.9g NMP solvent, stir at 30r / min for 80min, stir at high speed to break and disperse the particle agglomerates, finally add 2.09g SBR (50%), stir at 15r / min for 30min, adjust the viscosity after fully mixing, and obtain negative electrode slurry. Apply the slurry on copper foil, roll-form, and obtain negative electrode sheet.

[0067] The formed positive and negative electrode sheets are cut into positive electrode rolls and negative electrode rolls, the pole ears are welded on the electrode rolls, and a separator is added between the positive and negative electrode sheets for winding and assembly into a steel shell.

[0068] The assembled battery cells are baked, electrolyte is injected, and the batteries are sealed. The finished batteries are then divided into different capacities.

[0069] Embodiment 7:

[0070] Preparation of positive electrode: 6g of lithium iron manganese phosphate (LiMn x Fe 1-x-y M yPO4, x = 0.7), 0.95g SP, 1.51g PVDF dry powder, 0.32g TR-4045, 15r / min low speed dry mixing for 30min, until the dry powder is evenly mixed; add 6.31g NMP solvent, 12.62g CNT (5%) slurry, 20r / min slow stirring for 30min, scrape the material after stirring, add 7.33g NMP solvent, 20r / min medium and high speed stirring for 100min, observe the kneading state of the slurry and then determine to add 10.04g NMP solvent, 30r / min high speed stirring for 60min, measure the viscosity, fineness and solid content of the slurry out of the pot. After the solid content (64% ± 5%) and viscosity (7000-10000mpa.s) are qualified, the positive electrode slurry is coated on aluminum foil and roll-formed to obtain a positive electrode sheet.

[0071] Preparation of negative electrode sheet: Add 45g hard carbon, 26.98g 2.73% CMC glue, stir at low speed for 40min, scrape after stirring, 7.11g aqueous conductive agent solution (10%), 5g deionized water, knead and stir at 20r / min for 120min, mix evenly; add 1.9g NMP solvent, stir at 30r / min for 80min, stir at high speed to break and disperse the particle agglomerates, finally add 2.09g SBR (50%), stir at 15r / min for 30min, adjust the viscosity after fully mixing, and obtain negative electrode slurry. Apply the slurry on copper foil, roll-form, and obtain negative electrode sheet.

[0072] The formed positive and negative electrode sheets are cut into positive electrode rolls and negative electrode rolls, the pole ears are welded on the electrode rolls, and a separator is added between the positive and negative electrode sheets for winding and assembly into a steel shell.

[0073] The assembled battery cells are baked, electrolyte is injected, and the batteries are sealed. The finished batteries are then divided into different capacities.

[0074] The following is a performance test of the batteries prepared in Examples 1 to 7.

[0075] Low temperature rate test of the battery (referred to as low temperature performance): After the battery has been charged to capacity, it is left to stand for 24 hours, and then the battery is fully charged at a rate of 0.5C in the voltage range of 2.5-4.3V, and then discharged to 2.0V at a rate of 0.5C; then the battery is fully charged at 1C, and then placed in refrigerators at 0℃, -10℃, and -20℃ to discharge to 2.0V; the ratio of the discharge capacity at -20℃ to the discharge capacity at room temperature is the low temperature rate of the battery.

[0076] The normal temperature cycle life of the battery (referred to as cycle performance): After the capacity-fractionated battery has been left to stand for 24 hours, the battery is fully charged at a rate of 0.5C within the voltage range of 2.5 to 4.3V, and then discharged to 2.0V at a rate of 0.5C; then the battery is placed at room temperature, fully charged at a rate of 1C within the voltage range of 2.5 to 4.3V, and then discharged to 2.0V at a rate of 1C; repeat the above cycle.

[0077] As shown in the following Table 1, Table 1 is a comparison table of the low temperature performance of the lithium manganese iron phosphate batteries prepared in various embodiments.

[0078] Table 1

[0079]

[0080]

[0081] As shown in the following Table 2, Table 2 is a comparison table of the cycle performance of the lithium manganese iron phosphate batteries prepared in various embodiments.

[0082] Table 2

[0083]

[0084] As can be seen from Table 1, from Examples 1-7, the low-temperature performance of the high-performance lithium manganese iron phosphate battery provided by the present invention is improved as the content of the doped manganese material increases, but when the manganese content is too high, the low-temperature performance is improved to a certain extent, but the improvement is no longer obvious.

[0085] As can be seen from Table 2, from Examples 1-7, it can be obtained that the high-performance lithium manganese iron phosphate battery provided by the present invention gradually increases with the increase of the content of doped manganese material, but when the manganese content is too high, the Jan-Taylor effect occurs, and continuous charge and discharge is likely to cause manganese ions to dissolve and deposit on the surface of the negative electrode, destroying the SEI film, resulting in continuous regeneration and repair of the SEI film, thereby consuming a large amount of active lithium, causing capacity loss, a sharp drop in the battery cycle life, and unstable battery cycle performance.

[0086] Therefore, in combination with Table 1 and Table 2, it can be obtained from Examples 1-7 that when the manganese content of the high-performance lithium iron manganese phosphate battery provided by the present invention is too low, although the cycle life is relatively stable, its energy density is no different from that of the lithium iron phosphate battery, and its low-temperature performance is poor; as the content of the doped manganese material increases, the battery energy density continues to increase, and the battery low-temperature performance and cycle performance are improved; but when the manganese content is too high, the battery capacity and low-temperature performance are no longer significantly improved, and the cycle life and cycle stability are seriously affected, resulting in a sharp decrease in cycle life. In Examples 1-7, LiMn x Fe 1-x-y M yIn the lithium manganese iron phosphate material with PO4 structure, 0.4≤x≤0.7, 0≤y≤0.1, by optimizing the doping ratio of manganese material (ie, x value), the cycle life and cycle stability are improved, and the low temperature performance is excellent.

[0087] In the present invention, a better proportion of lithium manganese iron phosphate active material is formed by doping with manganese material, and then matched with a dry mixing process, also known as a "kneading" process. The basic process is to mix the active material, conductive agent and binder dry powder - add an appropriate amount of solvent to moisten - add solvent to disperse and crush large particles at high speed - and then dilute to adjust the viscosity of the slurry. When the slurry is stirred at ultra-high viscosity, the large shear force can more fully disperse the large particles, make its particle clusters smaller, and allow the conductive agent to evenly coat the active material. At the same time, it is also more conducive to the dissolution and stability of the binder. The slurry produced by this process has excellent viscosity, fineness, solid content consistency and stability performance, and the resistivity of the manufactured battery cell is low, and the battery cell capacity retention rate is higher.

[0088] The lithium manganese iron phosphate positive electrode material in the present invention not only inherits the characteristics of LFP, but also solves the adverse effects on battery performance when the manganese doping ratio is too high or too low. Its better manganese material doping ratio makes it have excellent low-temperature performance, better voltage platform and charge and discharge power, and can achieve higher energy density.

[0089] According to the lithium manganese iron phosphate battery of the present application, LiMn x Fe 1-x-y M y In the lithium manganese iron phosphate material with PO4 structure, 0.4≤x≤0.7, 0≤y≤0.1, by optimizing the doping ratio of manganese material (i.e., x value), its cycle life and cycle stability are improved, and its voltage platform is stably improved; and by adding highly adhesive adhesives and conductive agents with excellent conductive networks, the adhesion and conductivity of positive and negative electrode materials are improved, thereby significantly improving the cycle performance of the battery.

[0090] In summary, the high-performance lithium iron manganese phosphate battery and its preparation method provided by the present invention optimize the lithium iron manganese phosphate material, the positive electrode active material, optimize the contents of lithium and manganese in the lithium iron manganese phosphate, and optimize the doping ratio of the manganese material to obtain a lithium iron manganese phosphate battery with excellent performance such as energy density, cycle stability, and safety. The positive electrode slurry adopts a semi-dry process (i.e., oily slurry), and the negative electrode slurry adopts a wet process (i.e., aqueous slurry). The positive and negative electrode slurries produced by the two processes have better uniformity and are easy to control the humidity and temperature during the mixing process. The ratio of the active substances, conductive agents, and binders in the positive and negative electrode slurries is optimized, which improves the consistency and stability of the slurry, effectively improves the low temperature performance and energy density of the battery, and has excellent cycle performance.

[0091] The above description is only an implementation mode of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A high-performance lithium manganese iron phosphate battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and a steel shell, wherein the positive electrode sheet, the separator and the negative electrode sheet are wound and contained in the steel shell; the positive electrode sheet comprises a positive electrode current collector and a positive electrode slurry coated on the positive electrode current collector, the positive electrode slurry comprises a positive electrode active material, the positive electrode active material is lithium iron manganese phosphate, and the structural formula of the positive electrode active material is LiMn x Fe 1-x-y M y PO4, wherein 0≤x≤1, 0≤y≤1, and M is one or more of the transition metal elements Co, Ni, Mn, Zn, V and Ti.

2. The high performance lithium manganese iron phosphate battery according to claim 1, characterized in that: The structural formula of the positive electrode active material is LiMn x Fe 1-x-y M y In PO4, 0.4≤x≤0.7, 0≤y≤0.

1.

3. The high performance lithium manganese iron phosphate battery according to claim 1, characterized in that: The positive electrode active material is an inorganic phosphate with an olivine structure.

4. The high performance lithium manganese iron phosphate battery according to claim 1, characterized in that: The primary particle size of the positive electrode active material is 200-400 nm.

5. The high performance lithium manganese iron phosphate battery according to claim 1, characterized in that: The positive electrode slurry further includes a positive electrode conductor, a positive electrode binder, and a positive electrode dispersant. The positive electrode conductor includes one or more of CNT, SP, and graphene. The positive electrode binder is PVDF, and the positive electrode dispersant is TR-4045.

6. The high performance lithium manganese iron phosphate battery according to any one of claims 1 to 5, characterized in that: The negative electrode sheet includes a negative electrode current collector and a negative electrode slurry coated on the negative electrode current collector, the negative electrode slurry includes a negative electrode active material, a negative electrode conductive agent, a negative electrode thickener, and a negative electrode binder, the negative electrode active material includes one or more of graphite, soft carbon, and biomass hard carbon, the negative electrode conductive agent includes one or more of carbon nanotubes, conductive carbon black, and water-based graphene composite slurry, the negative electrode thickener is CMC, and the negative electrode binder is SBR.

7. A method for preparing a high-performance lithium manganese iron phosphate battery, characterized in that: The steps include: Step S10, preparing a positive electrode sheet: mixing powders of a positive electrode active material, a positive electrode conductive agent, a positive electrode binder PVDF, and a positive electrode dispersant, kneading and stirring them evenly; adding a portion of NMP solvent to wet the powder particles, dispersing the particle agglomerates under the action of high-speed shear force, so that the positive electrode conductive agent is evenly distributed, and the slurry is in a wet, viscous, soft mud state; After kneading, NMP solvent is added to adjust the viscosity and solid content of the slurry to form a black, moist and thick colloid, and then a positive electrode slurry of a PVDF / NMP oily system is prepared; the positive electrode slurry is coated on the positive electrode current collector, and roll-formed to obtain a positive electrode sheet; the positive electrode active material is lithium manganese iron phosphate, and the structural formula of the positive electrode active material is LiMn x Fe 1-x-y M y PO4, wherein 0≤x≤1, 0≤y≤1, and M is one or more of transition metal elements Co, Ni, Mn, Zn, V and Ti; Step S20, preparing the negative electrode sheet: mixing and stirring the negative electrode active material hard carbon and the negative electrode thickener CMC glue to make the slurry into a wet and viscous mud, adding the negative electrode conductive agent water-based graphene composite slurry and solvent, wetting and kneading the powder particles and controlling the slurry viscosity, and then adding the negative electrode binder SBR, dispersing the particle agglomerates under the action of high-speed shear force, so that the negative electrode active material and the negative electrode conductive agent are evenly distributed to form a light gray and viscous liquid, and preparing a negative electrode slurry of a hard carbon / CMC / SBR aqueous system, coating the negative electrode slurry on the negative electrode collector, and roller-forming to obtain a negative electrode sheet; Step S30, cutting the formed positive electrode sheet and negative electrode sheet into positive electrode rolls and negative electrode rolls, welding the pole ears on the positive electrode rolls and negative electrode rolls, adding a separator between the positive electrode sheet and the negative electrode sheet, winding them, and assembling them into a steel shell; Step S40, baking the assembled battery cells, injecting electrolyte into the steel shell and sealing the steel shell to obtain a finished battery, and then chemically dividing the finished battery into different capacities.

8. The method for preparing a high-performance lithium manganese iron phosphate battery according to claim 7, characterized in that: In step S10, the positive electrode conductive agent includes SP and CNT, and the weight ratio of the positive electrode active material, SP, CNT, positive electrode binder and positive electrode dispersant is 79.6:1.3:16.7:2:0.

4.

9. The method for preparing a high-performance lithium manganese iron phosphate battery according to claim 7, characterized in that: In step S20, the weight ratio of the solid content of the negative electrode active material, the negative electrode conductive agent, the negative electrode thickener, and the negative electrode binder is 94.95:1.5:1.35:2.

2.

10. The method for preparing a high-performance lithium manganese iron phosphate battery according to claim 7, wherein the tap density of the positive electrode active material is ≥ 0.8 g / cm 3 , with a specific surface area of ​​19-25m 2 / g; during the preparation of the positive electrode active material, the primary particle size of the added lithium source and manganese source is 60-100nm.